THE ROLE OF WEB QUEST TECHNOLOGIES IN DEVELOPING STUDENTS' INTERCULTURAL COMMUNICATION COMPETENCIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This study explores the impact of web quest technologies on enhancing students' intercultural communication competencies. Through the integration of interactive, internet-based quests in educational settings, students engage with diverse cultural materials, fostering a deeper understanding and appreciation of global perspectives. The research adopts the IMRAD structure, detailing the introduction, methodology, results, and discussion of findings, concluding with practical implications for educators.